2004
DOI: 10.1128/aem.70.9.5323-5330.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hexose Transport in Control of Glycolytic Flux in Saccharomyces cerevisiae

Abstract: The yeast Saccharomyces cerevisiae predominantly ferments glucose to ethanol at high external glucose concentrations, irrespective of the presence of oxygen. In contrast, at low external glucose concentrations and in the presence of oxygen, as in a glucose-limited chemostat, no ethanol is produced. The importance of the external glucose concentration suggests a central role for the affinity and maximal transport rates of yeast's glucose transporters in the control of ethanol production. Here we present a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 51 publications
11
117
1
2
Order By: Relevance
“…Elbing et al (2004) reported the glucose uptake rate as the determinant of respiratory metabolism in S. cerevisiae. The use of chimeric hexose transporters allowed for the reduction of the maximal glucose uptake rate, leading to the absence of ethanol production at low uptake rates (below 5 mmol g 21 h…”
Section: Discussionmentioning
confidence: 99%
“…Elbing et al (2004) reported the glucose uptake rate as the determinant of respiratory metabolism in S. cerevisiae. The use of chimeric hexose transporters allowed for the reduction of the maximal glucose uptake rate, leading to the absence of ethanol production at low uptake rates (below 5 mmol g 21 h…”
Section: Discussionmentioning
confidence: 99%
“…The absence of ethanol formation is particularly critical when S. cerevisiae is used for the production of heterologous proteins. A promising approach to obtaining yeast with a fully respiratory phenotype in sugar-containing industrial media such as molasses has been published by Elbing et al (82). They generated a yeast strain which is defective in the most important hexose transporter genes (HXT1 to -7) and expresses a chimeric hexose transporter.…”
Section: Food and Beverage Industrymentioning
confidence: 99%
“…It was mentioned in the previous section that recent attempts to abolish the Crabtree effect in yeast could be a novel avenue to reducing ethanol in beverages. Based on the approach of Elbing et al (82), a non-ethanol-producing wine yeast strain was developed by modifying hexose transporters (117). Moreover, introducing heterologous enzymes to increase NADH oxidation has been shown to reduce overflow metabolism, i.e., ethanol formation, in a wine yeast strain (121).…”
Section: Food and Beverage Industrymentioning
confidence: 99%
“…In another recent report (8), we presented a series of strains expressing functional chimeras composed to different degrees of the low-affinity (K m , 100 mM) and high-affinity (K m , 1 to 2 mM) transporters Hxt1 and Hxt7, respectively (28); one of the strains was KOY.TM6*P (27). Sugar uptake analysis data showed that the Tm6* protein in the KOY.TM6*P strain proved to be a high-affinity hexose transporter (27).…”
mentioning
confidence: 99%